Feasibility and safety of non-operative management of portal vein aneurysms: a thirty-five year experience. Issue 1 (January 2021) - Ahmed, Ola; Ohman, John W.; Vachharajani, Neeta; Yano, Motoyo; Sanford, Dominic E.; Hammill, Chet; Fields, Ryan C.; Hawkins, William G.; Strasberg, Steven M.; Doyle, Maria B.; Chapman, William C.; Khan, Adeel S.
Abstract: Background: Portal vein aneurysms (PVAs) are rare, though clinically challenging with post-operative mortality approaching 20% and no evidence-based treatment guidelines. We aim to describe our experience with PVAs and recommend optimum management strategies. Methods: Demographics and clinical details of patients with PVAs admitted to our institution from 1984 to 2019 were reviewed. Clinical presentation, management and outcomes were analysed. Results: PVAs were identified in 18 patients (median age 56 years, range 20–101 years; 13 female); 10 were incidental and 8 diagnosed during abdominal pain work-up. Median aneurysm diameter at diagnosis was 3.4 cm (1.8–5.5 cm), remaining unchanged at 3.5 cm (1.9–4.8 cm) during a 3.2-year follow-up (4 months-31 years). Aneurysm sites were the main portal vein (n = 12), porto-splenic-junction (n = 3), splenic-SMV-junction (n = 2) and right portal vein (n = 1). Thrombosis occurred in 4 patients; 3 developed clinically insignificant cavernous transformation. Two patients underwent surgery for abdominal pain. Postoperatively, one developed PV thrombosis and PVA recurrence occurred in the second. No aneurysm ruptures or mortalities occurred during follow-up. Conclusion: PVAs follow a clinically indolent course with structural stability and minimal complications over time. Non-operative management is feasible for most patients. Abdominal pain, large size or thrombosis don't appear to confer additional risks and should not, in isolation, merit surgical intervention.